Behind the Façades of an Aesopian Duck: The Quest for Authenticity in the Literary Forgeries of David Solway - Laurico, MaryAnne (Studies in Canadian Literature, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In both his collection Saracen Island: The Poetry of Andreas Karavis (2000) and the accompanying volume of “criticism,” An Andreas Karavis Companion (2000), David Solway creates, forges, imagines, and brings to life the fictitious contemporary Greek poet Andreas Karavis. Solway’s work is a palimpsest of strategically constructed identities, layers of truth mixed in with verifiable and unverifiable facts. He blurs the culturally constructed binary of authentic/inauthentic art by nodding toward Romantic notions of authenticity while underscoring the connection between poetic personae and the construction of authentic identity. His work invites readers to ask whether Solway’s stunting is a way to gain readership as an indie poet preoccupied with exposing literary hegemony in Canada, and to wonder where in these layers the authentic Solway can be found. Ultimately, his forgeries underscore the paradoxical belief in, and desperate quest for, an original, authentic existence.